Appropriateness of perioperative antibiotics in thyroid surgery - Yadav, Deepak; Dangol, Bhawana; Shrestha, Namita; Maharjan, Leison; Nepal, Ajit (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Most of the guidelines do not recommend routine antibiotics prophylaxis in clean head and neck surgery like thyroidectomy. In contrary to the recommendation, antibiotics are being routinely prescribed in perioperative period for various duration in many centers of Nepal. This study was aimed to find out the need of postoperative antibiotics in surgeries for thyroid related problems.Method: Records of all patients who had undergone surgery for thyroid related problems from Jan, 2019 to Sept, 2022 were retrospectively reviewed for patterns of antibiotic use, apart from preincision antibiotic, in postoperative period which was classified as group A – no antibiotics, group B – shorter course of antibiotics (≤3 days) and group C – longer course of antibiotics (>3 days). The occurrence of surgical site infection (SSI) was recorded.Result: During the study period, 77 patients underwent surgery for thyroid related problems, out of which five were excluded (records not found in four cases and one patient was ASA III). Two out of 72 (2.77 %) patients developed superficial incisional SSI which was managed conservatively. One patient in each group A (50) and group B (8) developed SSI.Conclusion: Postoperative antibiotics can be avoided safely even in our setup in clean head and neck surgeries like thyroidectomy without increase in the risk of SSI thus reducing the cost to the patients.